Problem-based learning: future challenges for educational practice and research - Dolmans, Diana H J M; De Grave, Willem; Wolfhagen, Ineke H A P; Van Der Vleuten, Cees P M (Medical education, 2005)
Context  Problem‐based learning (PBL) is widely used in higher education. There is evidence available that students and faculty are highly satisfied with PBL. Nevertheless, in educational practice problems are often encountered, such as tutors who are too directive, problems that are too well‐structured, and dysfunctional tutorial groups. Purpose  The aim of this paper is to demonstrate that PBL has the potential to prepare students more effectively for future learning because it is based on four modern insights into learning: constructive, self‐directed, collaborative and contextual. These four learning principles are described and it is explained how they apply to PBL. In addition, available research is reviewed and the current debate in research on PBL is described. Discussion  It is argued that problems encountered in educational practice usually stem from poor implementation of PBL. In many cases the way in which PBL is implemented is not consistent with the current insights on learning. Furthermore, it is argued that research on PBL should contribute towards a better understanding of why and how the concepts of constructive, self‐directed, collaborative and contextual learning work or do not work and under what circumstances. Examples of studies are given to illustrate this issue.